Pediatric esophageal perforation due to firearm injuries during the Syrian war and a new suture technique - Ahmet Atıcı; Mehmet Emin Çelikkaya; Çiğdem El; Bülent Akçora (Elsevier, 2018)
The incidence of esophageal perforation (EP) due to firearm injury (FAI) is markedly low compared with that occurring in other organs. The most frequently reported cause of EP is iatrogenic injuries. The incidence of EP due to penetrating injuries, such as FAI, is very rare and highly destructive. Here we report cases of EP due to FAI in childhood during the Syrian war and elucidate a new suture technique.